Fertilization capacity with rainbow trout DNA-damaged sperm and embryo developmental success - Perez-Cerezales, S. (2018)
Mammalian spermatozoa undergo a strong selection process along the female tract to guarantee fertilization by good quality cells, but risks of fertilization with DNA-damaged spermatozoa have been reported. In contrast, most external fertilizers such as fish seem to have weaker selection procedures. This fact, together with their high prolificacy and external embryo development, indicates that fish could be useful for the study of the effects of sperm DNA damage on embryo development. We cryopreserved sperm from rainbow trout using egg yolk and low-density lipoprotein as additives to promote different rates of DNA damage. DNA fragmentation and oxidization were analyzed using comet assay with and without digestion with restriction enzymes, and fertilization trials were performed. Some embryo batches were treated with 3-aminobenzamide (3AB) to inhibit DNA repair by the poly (ADP-ribose) polymerase, which is an enzyme of the base excision repair pathway. Results showed that all the spermatozoa cryopreserved with egg yolk carried more than 10% fragmented DNA, maintaining fertilization rates of 61.1+/-2.3 but a high rate of abortions, especially during gastrulation, and only 14.5+/-4.4 hatching success. Furthermore, after 3AB treatment, hatching dropped to 3.2+/-2.2, showing that at least 10% DNA fragmentation was repaired. We conclude that trout sperm maintains its ability to fertilize in spite of having DNA damage, but that embryo survival is affected. Damage is partially repaired by the oocyte during the first cleavage. Important advantages of using rainbow trout for the study of processes related to DNA damage and repair during development have been reported. Reproduction (2010) 139 989-997